The interventions of the Recovery and Resilience Plan in Italy: cities adaptation to climate change - Sgambati, Sabrina (TeMA - Journal of Land Use, Mobility and Environment, 2023)
Starting from the relationship between urban planning and mobility management, TeMA has gradually expanded the view of the covered topics, always following a rigorous scientific in-depth analysis. This section of the Journal, Review Notes, is the expression of a continuous updating of emerging topics concerning relationships among urban planning, mobility and environment, through a collection of short scientific papers. The Review Notes are made of five parts. Each section examines a specific aspect of the broader information storage within the main interests of TeMA Journal. This section of the Review Notes deals with the new frontiers of urban development through the lenses of the European program NextGenerationEU. In particular, this contribution deepens the topic of adaptation to climate change in cities, analysing the interventions proposed within the Italian National Recovery and Resilience Plan. The paper takes into account the recent PNRR strategies, projects, and initiatives aimed at coping with global warming effects in urban environments and with the increasing vulnerability of cities to climate events. Also, this paper provides an overview of the proposed projects and interventions in different Italian cities.